Bilateral synchronous presentation of Langerhans cell histiocytosis of maxilla and mandible: a rare case report and literature review - Anehosur, Venkatesh; Byadgi, Akshay A.; Narayana B., Sudeep; Sangam, Parinitha S.; Hephzibah, Rani (International Surgery Journal, 2026)
Previously known as histiocytosis X, Langerhans cell histiocytosis (LCH) is a rare haematological condition that primarily affects new-borns and young children. The uncontrolled activation and proliferation of normal antigen-presenting cells, specifically Langerhans cells, are the defining features of this condition. A positive immunohistochemistry result for CD1a/CD207 and S100 is the gold standard for a conclusive diagnosis. There are various therapy options available for individuals with LCH. Due to its comparatively low occurrence, little information is known about the epidemiology of LCH; cases are estimated to occur 3-5 times annually per million population. In this report, we have highlighted a case of 35-year-old adult who reported to the department with Bilateral synchronous gingival enlargements in maxilla and mandible. On clinical, radiological, histopathological (Incisional biopsy) and immunohistochemical examinations revealed a diagnosis of LCH. even though LCH incidence in adults is uncommon, LCH must be taken into account when evaluating multiple osteolytic bony jaw lesions in young adults that have an unclear aetiology. So here we present a rare case of Bilateral synchronous presentation of LCH of maxilla and mandible in adult with its management.